Documenting the structures of musical silencing and audibility: The South African Broadcasting Corporation's Central Record Acceptance Committee from 1986 to 1996. Issue 2 (2nd July 2016) - Jansen van Rensburg, Claudia
ABSTRACT: The article explores the censorship of music under apartheid South Africa as practised by the state broadcaster, the South African Broadcasting Corporation (SABC). The article suggests that while no formal government structures were in place to censor music per se (government censorship structures were primarily concerned with the restriction and surveillance of literature, film and the media), the SABC was the most dominant censor of musical production and dissemination on the apartheid state's behalf. The article argues, based on archival findings dating from 1986 to 1996, that the SABC's Central Acceptance Committee (CRAC), tasked to assess the suitability of musical items for broadcast, attempted to align itself with government censorship procedures but was placed in an ambiguous position with the gradual change in political climate from approximately 1990 to 1996 (the year in which the committee was dismantled). The data collected does therefore not reflect a censorship system functioning securely in the years of 'grand apartheid', but rather one that was beginning to disintegrate under the pressures of political reform. In addition, the article argues that music, unlike literature (that was assessed in the light of its 'artistic merit'), was censored without any particular aesthetic programme in mind.